Evaluating capacity development within the alchemy community development trusts towards achieving foundation tasks - Mapheto, Paula Phoebe Shibu (My University, 2020)
In 2011, Anglo American Platinum (AAP) launched a development initiative called Alchemy. Alchemy is the first social initiative launched by AAP that uses four Community Development Trusts (CDTs) and a Non-Profit Company to facilitate share ownership to develop and empower communities around its mining operations and the Labour Sending Areas. However, little is understood about the capacity needed to establish successful Trusts. To date, no evaluation has been conducted on how the trustees are navigating the Alchemy Foundation Phase against the mandate and tasks set out. This study aims to evaluate the capacity of four Alchemy CDTs to deliver on the first phase or “Foundation” tasks, as experienced by trustees. A qualitative research technique was used to gather insights into the Trustees' experiences in the interest of delivering the Foundation tasks. Semi-structured in-depth interviews were conducted with nine Trustees. The Results-Oriented Approach to Capacity Change (ROACH) tool (Boesen and Therkildsen, 2005) was used to evaluate the Trusts’ capacity. There was evidence that the CDTs’ capacity to deliver the Foundation tasks was supported by positive success factors. The enabling environment, both from a global and national perspective provided a conducive platform for the CDTs to be successful. The findings indicated significant capacity within the organisational set up of the Alchemy CDTs. The CDTs were fortunate to be supported up by a leading Platinum mining giant (AAP) which instituted robust legal frameworks and a well-researched structural design within Alchemy. The initiative appeared successful in attracting mature, highly skilled persons, some of whom have a history of working in development structures apart from Alchemy. The capacity was further strengthened by Trustees that found it rewarding to be involved with an initiative that aims to develop and empower underprivileged mine communities. The funding resources from AAP was acknowledged for sustaining the Alchemy Trusts’ mandate. However, capacity difficulties were experienced on matters related to the preparedness of CDTs to meet their development agenda. Evidence of this was seen in the weak system tools available to support the work of the CDTs (such as monitoring tools, reporting tools, impact assessment tools, operational procedures and performance management tools). The induction training provided limited guidance on good development practices that were needed by Trustees as the CDTs embarked on their development mandate. It also appeared that the Founder senior management had limited understanding of the development complexities experienced by the CDTs and, the beneficiaries lacked knowledge of the CDTs’ mandate, regulations, and governance procedures. As a result, these stakeholders had unrealistic expectations of the CDTs’ focus areas and the pace of project implementation. These capacity difficulties contributed to a power imbalance between the CDTs and the Shareholding Trust. Also, the Founder easily imposed ideas on the CDTs-an approach that Trustees felt unable to challenge. Further capacity hindrances were identified within the CDTs’ organisational culture that was found not to be inclusive to women and youth. The lack of locally based resources or local offices needed to support community liaison was viewed as a capacity constraint. Capacity issues were also identified within the incentive paradigm, the rewards and recognition component for both Founder and Independent Trustees need to be reviewed. This study concludes that while there was capacity within the CDTs in the Foundation Phase – there were considerable weaknesses which will hamper the next phase of Alchemy CDTs’ effectiveness. This is because the next phase, termed the Consolidation Phase, introduces a new class of Trustees (community representatives) and focuses more on the implementation of the development agenda. Therefore, this study makes the following key recommendations; •At the start of the Consolidation Phase, development tools should be introduced and/or strengthened to include reporting tools, performance tracking and monitoring tools and impact assessment. •The Consolidation Phase should be inaugurated by an in-depth induction training focusing on operational functions, role clarity, lessons learned from the Foundation Phase together with the legal and governance functions that will possibly be required by the less educated Community Trustees. The induction training should extend broader to include the Founder senior management and beneficiaries. •The introduction of Community Trustees will introduce a wealth of insights on the community dynamics. The CDTs should create an enabling environment to leverage the Community Trustees’ rich community knowledge and to allow real influence on decision-making. •The composition of the CDT boards both in the Foundation and in any future phases should be in compliance with the Deed. The inclusivity of women is an urgent priority. The inclusion of youth representatives should be considered. •The skills and knowledge of the operational structure incumbents must be adequately matched to the CDT’s tasks and key performance areas. •The incentives for both Founder and Independent Trustees should be reviewed to encourage performance. •In the Consolidation Phase, the Founder must be encouraged to step back in order to support the growing independence of the CDTs. The Founder must ensure comfort on the system tools that will track process and highlight when support is required
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science in Engineering, 2020